Cultural Perspectives of Millennials' Decision-Making Styles in Online Group Buying. Issue 4 (8th August 2022) - Klein, Andreas; Sharma, Varinder M.
Abstract: The spread of globalization and Internet-related technologies have contributed toward the emergence of convergence, divergence, and global consumer culture as three alternative perspectives to explain cross-cultural consumption, and yet no consensus has evolved. The study tests the veracity of the respective claims by comparing the relationships between the decision-making styles of U.S. and German millennials and their intentions to purchase from a cross-culturally cloned group-buying site popular in both countries. Results show that while there is a convergence of the novelty-fashion-conscious, price-conscious, "value for money, " recreational, hedonistic, and impulsive, careless decision-making styles of U.S. and German millennials, there is a divergence of their perfectionistic, high-quality-conscious, brand-conscious, "price equals quality", habitual, brand-loyal, and confused by overchoice decision-making styles. Taken together, the results support the prevalence of the global consumer culture approach. We offer implications toward building more comprehensive theoretical frameworks for analyzing cross-cultural consumption among millennials and for multinational website managers to improve their understanding of millennial consumption.